Analysis of Joged Kahyangan Works in Saxophone Recitals "Lintas Waktu" - Komalig, Yudi Novrian; Nugraha, Adinda Satria; Ruswanto, Yohanes (Jurnal Seni Musik, 2023)
This research aimed to describe the structure of the composition "Joged Kahyangan" by Dewa Budjana. This study employed qualitative approach, analyzing the musical score of the piece. The findings indicate that the composition's structure consists of several sections, including Introduction, A, Bridge, B, A’, Bridge, B’, A’’, Solo Drum, Solo Piano, Solo Saxophone, C, B’, and Coda. The piece utilizes the tonalities of E and D, with time signatures of 4/4 and 5/5. Saxophone playing techniques found in this composition include Arpeggio, Tongue, Legato, and Altissimo